Stock Market Returns and Inflation: Evidence from Other Countries - GULTEKIN, N. BULENT (Journal of Finance, 1983)
ABSTRACT This paper investigates the relation between common stock returns and inflation in twenty‐six countries for the postwar period. Our results do not support the Fisher Hypothesis, which states that real rates of return on common stocks and expected inflation rates are independent and that nominal stock returns vary in one‐to‐one correspondence with expected inflation. There is a consistent lack of positive relation between stock returns and inflation in most of the countries.